Screening of sorghum (Sorghum bicolor) genotypes for resistance to covered kernel smut (Sporisoriumsorghi) disease - Phiri, Lindsay (Midlands State University, 2017)
Covered kernel smut of sorghum caused by Sporisoriumsorghi is a major threat to sorghum production globally. This pathogen has been reported to attack sorghum resulting in yield losses as high as 75% on susceptible sorghum genotypes in Zimbabwe. Twelve sorghum genotypes were screened to determine the incidence and severity of covered kernel smut during the 2014/15 growing season. The trial was done under field conditions, where two artificial inoculation techniques namely seed dressing with dry teliospores and stem injection were used to observe the reaction of the sorghum genotypes. The experiment was set up using Randomised Complete Block Design with three replicates in the field. The disease incidence was highly distributed and it varied significantly (p<0.001) between the sorghum genotypes. A range of 0 – 40% incidence of the disease was recorded with SV-1 and ICSR 93034 having 0% and 40% respectively. Similarly, severity also followed the same trend as that of incidence with SV-1 having a mean score of 1 whilst ICSR 93034 had 4.667. NL 2015 produced the highest mean grain yield of 1.7467 tonnes/ha whilst NL 2014 had the lowest mean grain yield of 0.1903 tonnes/ha. The screening study suggests that farmers should grow sorghum genotypes SV-1, NL 2015 and ICSR 93024 which exhibited high levels of resistance to covered kernel smut disease.